2011
DOI: 10.1111/j.1467-629x.2011.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

A collective, undifferentiated accounting profession: an Australian study

Abstract: A study of 386 potential and current members of the accounting profession in Australia and South-East Asia provides evidence of the importance of three attributes -brand/reputation, international recognition of qualifications and career opportunities -in the decision to join a professional accounting body. While these attributes are important, logit regression models indicate that they are not discriminatory in the choice of professional body and suggest a perception of a collective, undifferentiated accountin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Past studies also found that perceived benefits were a major factor for sustaining membership (Inglis et al. ; Markova et al. ), which was consistent with the findings of this study.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Past studies also found that perceived benefits were a major factor for sustaining membership (Inglis et al. ; Markova et al. ), which was consistent with the findings of this study.…”
Section: Discussionsupporting
confidence: 92%
“…Drawing from previous research (Inglis et al. ; Knoke ), we used nine items to measure personal benefit: “access to career information and employment opportunities,” “access to products, services, and suppliers,” “a reference directory of members/practitioners,” “certification/credentialing,” “opportunities for you to network with other professionals in your field,” “opportunities to gain leadership experience,” “member discounts,” “access to the most up‐to‐date information available in your field,” and “professional development or educational program offerings.”…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations